Gorbachev vs the Soviet power structure: Liberalization of Media Control (Progress Annals: Journal of Progressive Research, 2023)
This article discusses changes in the media policy of the Soviet Union since 1985. In this, the political path of the new general secretary of the Communist Party, M.S. Gorbachev, and the change of censorship, which has been preserved for years, will be highlighted. In politics, opposite political situations of press and power structures are observed